1998
DOI: 10.1002/(sici)1521-4141(199811)28:11<3530::aid-immu3530>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of protective humoral (Th2) and cell-mediated (Th1) immune responses against herpes simplex virus-2 through co-delivery of granulocyte-macrophage colony-stimulating factor expression cassettes

Abstract: Granulocyte-macrophage colony-stimulating factor (GM-CSF) could in theory attract antigen-presenting cells in muscle following intramuscular DNA immunization, resulting in enhanced antigen-specific immune responses. Thus, such adjuvants could constitute an important addition to a herpes vaccine by amplifying specific immune responses. Here we investigate the utility of GM-CSF cDNA as a vaccine adjuvant for herpes simplex virus (HSV)-2 in a mouse challenge model. GM-CSF cDNA co-injection enhanced levels of spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
46
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 45 publications
(63 reference statements)
6
46
1
Order By: Relevance
“…Most groups concluded that GM-CSF could activate both Th1 and Th2 immune responses whereas others reported that GM-CSF biased immune response toward either a Th1 or a Th2 response. [13][14][15] Moreover, Kusakabe et al 19 demonstrated that the timing of GM-CSF expression in the context of plasmid administration influenced the Th1/Th2 response. GM-CSF administration before target gene inoculation polarized the response to a Th2 type, whereas a Th1 type response could be induced when GM-CSF was administered after target gene inoculation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most groups concluded that GM-CSF could activate both Th1 and Th2 immune responses whereas others reported that GM-CSF biased immune response toward either a Th1 or a Th2 response. [13][14][15] Moreover, Kusakabe et al 19 demonstrated that the timing of GM-CSF expression in the context of plasmid administration influenced the Th1/Th2 response. GM-CSF administration before target gene inoculation polarized the response to a Th2 type, whereas a Th1 type response could be induced when GM-CSF was administered after target gene inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…10 The adjuvant activity of GM-CSF has been demonstrated in several models with antigens that generally have a low immunogenicity. [11][12][13] GM-CSF has been reported to increase both humoral and cellular immune responses, 14,15 as well as to skew the Th1/Th2 balance. It is well accepted that GM-CSF acts as an adjuvant to enhance the immune response against the target antigen of interest; however, the ultimate effects of GM-CSF are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is logical that linking antigen and GM-CSF expression closely in vivo may provide a more conducive microenvironment for the uptake and presentation of antigen by dendritic cells or macrophages (53). Similarly, plasmids coding for IL-4 have also been used to preferentially augment B-cellmediated Th2 responses and Ig class switching (15,16,49).…”
Section: Discussionmentioning
confidence: 99%
“…The human GM-CSF pDNA was included in the vaccine to increase the immunogenicity as GM-CSF is known to attract dendritic cells to the site of administration and enhance the maturation of dendritic cell precursors which play an important role in antigen presentation. [19][20][21][22][23][24] While co-administration of GM-CSF pDNA has been demonstrated to enhance the immunogenicity of pDNA vaccines, [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] the overexpression of GM-CSF in transgenic mice has been demonstrated to result in adverse pathology associated with overaccumulation of macrophages in tissues, accumulation of macrophages in the peritoneal and pleural cavities, retinal damage, muscle wasting, and a fatal tissue damage syndrome. 37 Thus, the inclusion of GM-CSF in the vaccine raised several important theoretical safety concerns which had to be addressed before the vaccine could be taken into a clinical trial with healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%